ApoC1 promotes glioma metastasis by enhancing epithelial-mesenchymal transition and activating the STAT3 pathway. (4th March 2023) - Liang, Rui; Zhang, Guofeng; Xu, Wenhua; Liu, Weibing; Tang, Youjia
ABSTRACT: Objective: One of the apolipoprotein's members, apolipoprotein C1 (ApoC1), is critical in the metabolism of both very-low-density lipoprotein (VLDL) and high-density lipoprotein (HDL) cholesterols. Multiple studies have recently revealed that ApoC1 may be a viable therapeutic target in solid malignancies. However, the motor protein ApoC1ʹs specific role and mechanism in glioblastoma remain unknown. Methods: In this study, the Cancer Genome Atlas (TCGA) database was used to look at the level of ApoC1 in glioma tissues and normal tissues, as well as how it related to the prognosis of glioma. Glioma cell lines (U87 and U251) were subjected to a wide range of experiments to determine the involvement of ApoC1 in cell proliferation, migration, and invasion. Results: Cell proliferation, migration, and invasion decreased in glioma cell lines when ApoC1 was silenced. Furthermore, ApoC1 increased glioma cell metastasis through the epithelial-mesenchymal transition (EMT), while ApoC1 deletion reduced this impact. Additionally, APOC1 influenced the evolution of glioma by affecting the STAT3 pathway. In addition, APOC1 knockdown reduced the activation of the phosphorylated-total signal transducer and activator of transcription (STAT3) in the glioma cells. ApoC1-induced glioma cell metastatic ability was prevented by niclosamide (a STAT3 inhibitor). Conclusions: These results uncover that ApoC1 may serve as a biomarker or therapeutic target for future fundamental study or clinical treatment of glioma.